Biomarkers in breast cancer Part II: protein, DNA, cell adhesion and drug resistance markers - Ślubowski, Tadeusz; Ślubowska, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2007)
The second part of the two-part review on breast cancer biomarkers, will consider information on new developments in diagnosis and treatment of breast cancer, which are inherently related to the results of scientific achievements in molecular and cell biology. This overview describes current knowledge, dominant trends and problems related to biomarkers in breast cancer. It stresses the importance of protein markers: cyclines, proteins of invasiveness i.e. aspartile, serine, cysteine and metalloproteinase, DNA repairing processes related to methylation; as well as adhesive proteins: E-cadherine/catenine complex, CD44, and integrines. Other biomarkers such as CHEK2, encoding phase G2 kinase – playing role in DNA repairing – and polymorphic epithelial mucines Muc1 and Muc2, as well as drug resistance markers are also described. The overview deals with problems related to the development of verifiable biological markers due to technical and methodological obstacles and, amongst other low concentrations of cancer proteins, negligible structural differences between cancerous and healthy subject proteins, and lack of tissue and organ marker specificity, required for primary cancer site identification.